Bad leadership what it is, how it happens, why it matters - Kellerman, Barbara (Boston Harvard Business School Press, 2004)
How is Saddam Hussein like Tony Blair? Or Kenneth Lay like Lou Gerstner? Answer: They are, or were, leaders. Many would argue that tyrants, corrupt CEOs, and other abusers of power and authority are not leaders at all--at least not as the word is currently used. But, according to Barbara Kellerman, this assumption is dangerously naive. A provocative departure from conventional thinking, Bad Leadership compels us to see leadership in its entirety. Kellerman argues that the dark side of leadership--from rigidity and callousness to corruption and cruelty--is not an aberration. Rather, bad leadership is as ubiquitous as it is insidious--and so must be more carefully examined and better understood. Drawing on high-profile, contemporary examples--from Mary Meeker to David Koresh, Bill Clinton to Radovan Karadzic, Al Dunlap to Leona Helmsley--Kellerman explores seven primary types of bad leadership and dissects why and how leaders cross the line from good to bad. The book also illuminates the critical role of followers, revealing how they collaborate with, and sometimes even cause, bad leadership. Daring and counterintuitive, Bad Leadership makes clear that we need to face the dark side to become better leaders and followers ourselves. Barbara Kellerman is research director of the Center for Public Leadership and a lecturer in public policy at the Kennedy School of Government, Harvard University.
Includes bibliographical references (p. [245]-270) and index.
Keywords: Leadership